Identifikasi Sungai Bawah Tanah Berdasarkan Nilai Resistivitas Batuan Pada Danau Karst Tarusan Kamang, Kabupaten Agam. - Yuyu Fajriyatil Husni; Ansosry Ansosry (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Tarusan Kamang Lake is an area suspected of being a karst area and has an underground river. This is due to the presence of the lake that only appear or fill with water at certain times. For this reason, a research using geoelectric resistivity method with Wenner-Schlumberger configuration was used to obtain a 2D and 3D subsurface model. The retrieval of data is using by three measurement with a length of each track is 188 meters and the space is 4 meters. The results of measurement and interpretation of the data show that there are 4 types of constituent rock layers, namely sandstone clay, filite, quartzite and limestone. Based on 2D resistivity cross section models found a layer that has a tendency to form a tunnel that is in the layer of carbonate or limestone which has a range of resistivity values around 1.019-10.485 Ωm. This contour pattern is thought to be underground river passageways. This contour pattern is found on tracks 1, 2 and 3. This layer is found in the northwest direction towards the southeast at a depth of about 20-30 meters more than the surface. This carbonate rock layer is thought to have caprock or capsrock which is an underground river structure. Keywords:  Karst, Geoelectric, Resistivity, Carbonate, Capsrock.